RANCANG BANGUN SISTEM INFORMASI EMOSI SISWA MENGGUNAKAN EMOTICON BERBASIS WEB STUDY KASUS PADA SDIT BUNAYYA PERMATA TANGERANG - Sri Mulyati; Muhammad Aji Khoirun (University of Muhammadiyah Tangerang, 2019)
SDIT BUNAYYA is a private elementary school located in the Pasarkemis region of Tangerang Regency. Character-based SDIT Bunayya that pays attention to students' emotions to find out the development of students.In SDIT Bunayya in emotional data students still use the manual in writing to take time when reporting and when they want to observe student emotions.Thus the author tries to design an emotional data processing system for students using website-based emoticons that can help the process of data collection of teacher and student attendance and recording emotions for students during learning in school. In developing this system the author uses the PHP programming language with the concept of MVC (Model, View, Controller) to make it easier in its development with the CodeIgniter framework, System Analysis Methods using Object Oriented Analysis and Design (OOAD) and use UML (Unified Modeling Language) as a tool and the design method uses the waterfall model.The construction of this data processing system begins with the process of analyzing system requirements and is followed by a system design planning process based on the results of the needs analysis. The last stage of this drafting process is the implementation of the system into a new system. In this final assignment, it can be concluded that the system built to help the emotional data collection process can display the results of handling emotional information of students for the Principals of SDIT Bunayya, Homeroom Class and Teacher Budi Pekerti at SDIT Bunayya.